KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA GURU (KAJIAN DARI ASPEK ONTOLOGI) - Anitia Fadhila Bumay; Sudjarwo Sudjarwo; Muhammad Nurwahidin; Bujang Rahman (Bajang Institute, 2022)
This article aims to examine from the ontological aspect the role of the school principal on teacher performance. Literature review is the method used in this study where data collection was carried out using articles collected from 2017 to 2022. The reference articles were 15 national articles obtained from Google Scholar with the search